Immunomodulatory, antioxidant and anti-tumor capacity of acidic polysaccharides from Euglena gracilis. - Casas Arrojo, Virginia; Ortega Rodríguez, Alicia; Arrojo-Agudo, María Ángeles; Abdala-Díaz, Roberto Teófilo (My University, 2018)
Euglena sp. is a microalga producer of important molecules for the Biotechnology industry, since it is a producer of substances such as vitamins A, C and E, essential amino acids, polyunsaturated fatty acids, β-carotenes and paramilon (β-1,3-glucan). It has a modulating effect on the immune system, moderates blood glucose and the response to insulin, has anti-tumor activity and a cholesterol-lowering effect. In addition, its sulphated derivatives have anti-HIV activity. The present study was carried out with the objective of determining the immunomodulatory, antioxidant and anticancer activity of the acid polysaccharides extracted from Euglena gracilis. MTT colorimeter tests were carried out for the analysis of cytotoxicity on healthy cell lines murine macrophages (RAW 264.7) and human gingival fibroblasts (HGF-1) and for the anticancer activity cell lines were used colon cancer (HCT-116), breast cancer (MCF-7) and human leukemia (U-937) .The polysaccharide concentration at which cell survival was reduced by half (IC50) was estimated with these assays, showing that these polysaccharides have antitumor activity mainly on U-937 cells. (IC50 = 0.027 mg ml-1) against HCT-116 cells (IC50 = 0.036 mg ml-1) and MCF-7 (IC50 = 0.11 mg ml-1) An immunological test was performed to see the immunomodulatory capacity of the polysaccharides with which the production of proinflammatory cytokines IL-6 and TNF-α was determined by macrophages RAW 264.7 It was observed that these polysaccharides have a great stimulating capacity in the synthesis of these interleukins. Antioxidant capacity was (7.19 μmol TE g-1). In agreement with these results, it is suggested that E. gracilis polysaccharides could be considered for future studies as potential nutraceuticals that require their application when the activation of macrophages is needed.
Keywords: Macroalgas; Euglena gracilis; Polysaccharides; Immunomodulation; Antioxidant capacity; Anti-tumor activity; U-937; HTC116; RAW 264.7; HGF-1